Geoarchaeology and chronostratigraphy of the Lac du Puy intraurban protohistoric wetland, Corent, France. Issue 5 (14th April 2018) - Mayoral, Alfredo; Peiry, Jean‐Luc; Berger, Jean‐François; Ledger, Paul M.; Depreux, Bruno; Simon, François‐Xavier; Milcent, Pierre‐Yves; Poux, Matthieu; Vautier, Franck; Miras, Yannick
Abstract: This paper presents the first results of the geoarchaeological study of an unusual hilltop wetland, located within the protohistoric proto‐urban site of Corent in the French Massif Central. This small depression offers an exceptionally local sedimentary record that provided valuable data on long‐term human–environment interactions, as well as proto‐urbanization of the first millennium B.C.E. Field survey revealed a major archaeological discovery: a large ensemble of 114 Iron Age storage pits excavated in clayey deposits. The geoarchaeological analysis of stratigraphic logs and cross‐sections completed by geophysical survey and radiocarbon dating allowed us to refine the chronology of these structures. Here, we suggest these structures are probably contemporary with the Hallstatt occupation of the site (600–425 B.C.E.), consistent with the emergence at Corent of a short‐lived proto‐urban environment during this period. These investigations also allowed us to characterize the main evolution phases of the basin and the diversity of human impacts from first disturbance in the Early Neolithic to its final destruction in the Roman period. These findings highlight the nonlinear nature of the socio‐environmental interactions and the definitive shift to an "anthroposystem" as a consequence of major disturbance in the first Iron Age, centuries before the development of urban settlements in the oppida period.